Igbo Nationalism and Biafra - Harnischfeger, Johannes (AAeO - Afrikanistik-Aegyptologie-Online, 2011)
When I was living in Igboland in 1993 and from 1994 to 1996, there was not much talk about Biafra, the secessionist republic that had been defeated by the Nigerian army in 1970. Not one Igbo politician suggested that his or her people in the southeast of Nigeria should secede again and proclaim a second Biafra. Since 1984, Nigeria had been ruled by the military, and political hopes focused on a return to democracy. Democracy did come in 1999, but it proved a big disappointment. It did not end the marginalisation of the Igbo but led to an increase in the number of ethnic and religious clashes, with Igbo ’migrants’ in northern Nigeria as the main victims. It was Nigeria’s fourth transition to democracy, and the Igbo lost out again. When I returned to Igboland for brief visits between 2000 and 2007, the option of a new Biafra was widely discussed. Many of my former colleagues at the University of Nsukka seemed to be in favour of the secession project. I talked to supporters of the main separatist organisation, Movement for the Actualisation of a Sovereign State of Biafra (MASSOB), and I discussed the project with members of Ohanaeze, a loose association of Igbo politicians, most of whom had distanced themselves from radical secessionism. In order to learn more about the resurgence of Igbo nationalism, I collected Igbo periodicals. A few of them, such as the New Republic, resembled newspapers; others, like News Round, Eastern Sunset or Weekly Hammer (with eight pages in A4 size), looked more like political pamphlets. Street vendors used back issues as wrapping paper, so they were easy to get. Most of them had been edited not in Igboland, but in Lagos, Nigeria’s commercial centre and former capital which is home to a huge Igbo diaspora. Though written in English, these publications are addressed exclusively to an Igbo readership, discussing global and domestic affairs from a nationalist point of view. Articles printed here, no matter their topic, are nationalist in the sense that they assess things from the standpoint of Igbo interests. The same is true of many articles on Igbo websites and of some books and brochures written for an Igbo audience. Another source of information on Igbo nationalism are statements by Igbo governors, ministers, members of parliament and other professional politicians who are quoted in newspapers, such as Vanguard or Guardian, and in weekly magazines such as Newswatch, Tell or The News – all with a Nigeria-wide circulation and a multi-ethnic readership. Nigeria’s papers and magazines are among the best in Africa. They try to be balanced in their coverage of ethnic conflicts, and they give reliable information. The same cannot be said of periodicals produced by Igbo nationalists. They provide space for Igbo all over the world to voice their opinions, and they tolerate much controversy, but they are not accurate when reporting facts.